2021
DOI: 10.3389/fimmu.2020.583652
|View full text |Cite
|
Sign up to set email alerts
|

G Protein-Coupled Receptor 109A Maintains the Intestinal Integrity and Protects Against ETEC Mucosal Infection by Promoting IgA Secretion

Abstract: Several studies have reported an intricate link between the G protein-coupled receptor 109A (GPR109A) and intestinal health. Upon activation, induced by butyric acid and β-hydroxybutyric acid, GPR109A regulates the expression of tight junction proteins, exerts anti-inflammatory effects, and maintains the integrity of the intestinal barrier. However, its function and the mechanism of action in combating the infection caused by exogenous pathogenic microorganisms remain unclear. This study established an animal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…Herein, our results showed that a smaller villus height, larger crypt depth, and smaller VCR (the ratio of villus height to crypt depth) values were observed in the jejunum and duodenum of piglets in the GPR109A antagonist group than those in the niacin supplementation group. Consistently, a recent study reported that GPR109A −/− mice have severe intestinal structural damage [ 42 ]. Our results thus indicated that blocking GPR109A had a negative effect on intestinal morphology in weaned piglets.…”
Section: Discussionsupporting
confidence: 75%
“…Herein, our results showed that a smaller villus height, larger crypt depth, and smaller VCR (the ratio of villus height to crypt depth) values were observed in the jejunum and duodenum of piglets in the GPR109A antagonist group than those in the niacin supplementation group. Consistently, a recent study reported that GPR109A −/− mice have severe intestinal structural damage [ 42 ]. Our results thus indicated that blocking GPR109A had a negative effect on intestinal morphology in weaned piglets.…”
Section: Discussionsupporting
confidence: 75%
“…The collected tissues were weighed and homogenized in BHI broth. Homogenates were plated on kanamycin containing MAC agar plates for ETEC counts ( 40 ). Results were expressed as log of colony-forming units (CFU) per gram of organ.…”
Section: Methodsmentioning
confidence: 99%
“… 37 Presence of GPR109a was also shown to protect against experimental Escherichia coli (ETEC) infection, secretory IgA responses, and intestinal barrier integrity. 38 Sivaprakasam et al provided a detailed review of SCFA receptors. 39 …”
Section: Scfa and G-protein Coupled Receptorsmentioning
confidence: 99%